Optimalisasi Perilaku Hidup Bersih Dan Sehat (Phbs) Masyarakat Melalui Edukasi Pola Konsumsi - Fadhil, Muhammad Luthfi Irsyadul; Al Kahfi, Muhammad; Zandy, Rozan Kusuma; Fathurrahman, Farhan; Susilo, Muhammad Wangsa Putranto; Afrilia, Ananda; Nafasari, , Dyah Linda Syafina; Sulistyowati, Yuyun; Razani, Athaya Fairuz Damalika; Khasanah, Oktavia Putri; Nurdianto, Talqis (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The application of a healthy and clean lifestyle in daily life can determine the sustainability of a community’s well-being. A clean and healthy lifestyle can begin with the cleanliness and health of the household kitchen in each family. However, many people still do not pay attention to this lifestyle. For example, some people in Sarwodadi, Pejawaran, Banjarnegara, still neglect the cleanliness and health of their household kitchens. The kitchen is a place for preparing and serving food to the family. The cleanliness and health of the kitchen and food processing directly affect the family members' health. This community service program aims to raise awareness and understanding among PKK (Family Welfare Program) mothers regarding Clean and Healthy Living Behavior (PHBS) through education on healthy consumption patterns of side dishes to improve family health quality. The methods used include interactive counseling, distribution of educational posters, and a follow-up program called "Healthy Kitchen," which involves home visits to PKK mothers for further education on balanced nutrition. The results of this program show an increase in understanding and awareness among PKK mothers about the importance of personal hygiene, environmental cleanliness, and healthy eating habits. Most PKK mothers reduced their consumption of instant food and began paying more attention to the cleanliness of their home environment. Success indicators were measured through direct observations, interviews, and evaluations, which showed active community participation in applying PHBS. The main challenge in this program was changing old habits and limited access to nutritious food. Therefore, the proposed follow-up actions include providing digital educational modules, regular monitoring, and collaboration with health centers to strengthen the continuous implementation of PHBS. With a consistent and structured approach, it is hoped that this program will have a positive impact on creating healthier and empowered families.